Isolated Splenic Hydatid Disease. (9th January 2011) - Dilli, Alper; Tatar, Idil Güneş; Ayaz, Umit Yasar; Hekimoglu, Baki
Abstract : Hydatid disease (HD) continues to be a significant health problem in areas where animal husbandry is common but no proper veterinary control exists. The involvement of the spleen in HD is rare, and isolated splenic involvement is even less common. In this case report, we present isolated splenic HD in a 26-year-old female with complaint of abdominal pain, and we discuss some of the clinical aspects of HD. Evaluation of the patient with ultrasonography, computed tomography, and magnetic resonance imaging revealed the presence of an isolated splenic HD as a multivesicular cystic mass located near splenic hilus, measuring12 × 11 cm. No other organ or system involvement could be demonstrated.